Worldwide experience of homozygous familial hypercholesterolaemia: retrospective cohort study. Issue 10326 (19th February 2022) - Tromp, Tycho R; Hartgers, Merel L; Hovingh, G Kees; Vallejo-Vaz, Antonio J; Ray, Kausik K; Soran, Handrean; Freiberger, Tomas; Bertolini, Stefano; Harada-Shiba, Mariko; Blom, Dirk J; Raal, Frederick J; Cuchel, Marina; et al.
Summary: Background: Homozygous familial hypercholesterolaemia (HoFH) is a rare inherited disorder resulting in extremely elevated low-density lipoprotein cholesterol levels and premature atherosclerotic cardiovascular disease (ASCVD). Current guidance about its management and prognosis stems from small studies, mostly from high-income countries. The objective of this study was to assess the clinical and genetic characteristics, as well as the impact, of current practice on health outcomes of HoFH patients globally. Methods: The HoFH International Clinical Collaborators registry collected data on patients with a clinical, or genetic, or both, diagnosis of HoFH using a retrospective cohort study design. This trial is registered with ClinicalTrials.gov, NCT04815005 . Findings: Overall, 751 patients from 38 countries were included, with 565 (75%) reporting biallelic pathogenic variants. The median age of diagnosis was 12·0 years (IQR 5·5–27·0) years. Of the 751 patients, 389 (52%) were female and 362 (48%) were male. Race was reported for 527 patients; 338 (64%) patients were White, 121 (23%) were Asian, and 68 (13%) were Black or mixed race. The major manifestations of ASCVD or aortic stenosis were already present in 65 (9%) of patients at diagnosis of HoFH. Globally, pretreatment LDL cholesterol levels were 14·7 mmol/L (IQR 11·6–18·4). Among patients with detailed therapeutic information, 491 (92%) of 534 received statins, 342 (64%) of 534 received ezetimibe, and 243 (39%) of 621 received lipoprotein apheresis. On-treatment LDL cholesterol levels were lower in high-income countries (3·93 mmol/L, IQR 2·6–5·8) versus non-high-income countries (9·3 mmol/L, 6·7–12·7), with greater use of three or more lipid-lowering therapies (LLT; high-income 66% vs non-high-income 24%) and consequently more patients attaining guideline-recommended LDL cholesterol goals (high-income 21% vs non-high-income 3%). A first major adverse cardiovascular event occurred a decade earlier in non-high-income countries, at a median age of 24·5 years (IQR 17·0–34·5) versus 37·0 years (29·0–49·0) in high-income countries (adjusted hazard ratio 1·64, 95% CI 1·13–2·38). Interpretation: Worldwide, patients with HoFH are diagnosed too late, undertreated, and at high premature ASCVD risk. Greater use of multi-LLT regimens is associated with lower LDL cholesterol levels and better outcomes. Significant global disparities exist in treatment regimens, control of LDL cholesterol levels, and cardiovascular event-free survival, which demands a critical re-evaluation of global health policy to reduce inequalities and improve outcomes for all patients with HoFH. Funding: Amsterdam University Medical Centers, Location Academic Medical Center; Perelman School of Medicine at the University of Pennsylvania; and European Atherosclerosis Society